Effect of Piping Configuration on Determining Alarm Response Time in HP Scrubber Using Dynamic Simulation - In Jumanda Kasdadi; Fahmi Nur Listiani; Gianistri Maulani; Yanis Fitrianti (Fluida, 2023)
The HP scrubber is an equipment used to separate liquid from gas in the oil and gas industry. The low liquid level in the vessel is one of the abnormal conditions in the HP scrubber, a blowby gas event will happen because of a low level. So, the controller level indicator is required to prevent system damage and workplace accidents. The alarm response time is calculated in order to avoid an accident. To determine the alarm response time for a HP scrubber, a dynamic process simulation method can be used using Aspen HYSYS version 12. In a process simulation modeling also requires a process description that can describe real-world conditions, one of which is the condition of the existing piping in the system. Failure scenarios caused a process to have abnormal conditions, allowing the alarm response time to be calculated, and it can be modelled by using the event scheduler facility In Aspen HYSYS. The HP scrubber's maximum alarm response time without pipe segments and with the addition of 16 m pipe segments are 2.42 minutes and 2.56 minutes. Meanwhile, the time from alarm to failure on the HP Scrubber without and with the addition of 16 m pipe are 13.60 minutes and 28.70 minutes, respectively. So, the length of segment pipes added to the pipe configuration does not really affect the alarm response time. However, it can affect the time until a process failure occurs.